Variations in formation of median nerve: a cadaveric study - Hada, Shanta; Kadel, Muna; Pandit, Tinku Kumari; Basnet, Kishore Singh (Journal of Chitwan Medical College, 2020)
Background: Median nerve is generally formed in axilla, as one of the branch of brachial plexus. It is formed by the union of medial and lateral roots which are the branches of medial and lateral cord respectively. The knowledge of origin, course and area of distribution of median nerve is important for the anatomist, the neurologist and also for correction of traumatic injuries that are related to brachial plexus. The main objective of this study is to observe different variations in median nerve formation in cadavers.Methods: A descriptive cross-sectional study was conducted in 25 formalin fixed adult human cadavers in the Department of Anatomy, KIST Medical College and Teaching Hospital, Lalitpur Ethical approval was taken. Altogether, 50 specimens were enrolled in the study by convenient sampling method. The calculation was done using Statistical Package for Social Sciences version 20 (SPSS).Results: In this study the formation of median nerve was observed to be normal in 78% of the cases. In 20% cases three roots were forming the median nerve and in 2% cases four roots were present. Among these variations in 18% cases the additional roots were observed to be given by the lateral cord of the brachial plexus.Conclusions: This study concludes that most of the median nerve forms in axilla by the union of two roots with few variations.